PERTIMBANGAN PUTUSAN HAKIM DALAM PERKARA PIDANA ANAK PENYAKAHGUNAAN NARKOTIKA DENGAN UU SPPA - FRIJANTO, MOCHAMAD ARIEF (Jurnal HUKUM BISNIS, 2026)
This article aims to analyze the judge's considerations in deciding a drug abuse case involving a child, based on Decision Number 1/Pid.Sus-Anak/2023/PN Sda. This study uses a normative juridical method with a case approach. Data sources consist of primary and secondary legal materials collected through literature and document studies. The analysis was conducted using deductive reasoning, namely drawing conclusions from general principles to specific cases. The results of the study indicate that the judge's considerations in the case were basically in accordance with the Juvenile Criminal Justice System Law (UU SPPA). The evidentiary process was also deemed to fulfill the elements of the article charged by the Public Prosecutor in accordance with the provisions of Article 183 of the Criminal Procedure Code. In addition, the trial implementation followed the principles of child protection as stipulated in the UU SPPA, namely ensuring that children are tried through the Juvenile Criminal Justice System. However, this study found weaknesses in the judge's decision, as several important principles and provisions of the UU SPPA were ignored. This results in the verdict being deemed inappropriate and tending to burden the child defendant, contradicting the principle of child protection in the judicial process. Therefore, this article emphasizes the importance of applying the principle of the best interests of the child in every decision in criminal cases involving children. Keywords: Children in Conflict with the Law, Drug Abuse, Child Protection Act